2011
DOI: 10.1007/s10570-011-9628-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective recovery of gold(III) using cotton cellulose treated with concentrated sulfuric acid

Abstract: Novel utilization of cotton cellulose was developed by chemically modifying with concentrated sulfuric acid to prepare a novel kind of adsorption gel for gold. The adsorption behaviors of the gel were investigated for various metals from acidic chloride media. The gel was found to be highly selective for Au(III) over other precious and base metals tested over the whole concentration range of hydrochloric acid. The maximum adsorption capacity for Au(III) was evaluated as 6.21 mmol/g at 303 K. The amount of adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Therefore, the search for environmentally benign and low cost biosorbent materials for gold recovery is urgent. Since the last few years researches on biosorbents for gold recovery from aqueous solutions were concerned with tannin, microorganism, agricultural wastes, algae, polysaccharide, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the search for environmentally benign and low cost biosorbent materials for gold recovery is urgent. Since the last few years researches on biosorbents for gold recovery from aqueous solutions were concerned with tannin, microorganism, agricultural wastes, algae, polysaccharide, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…That is, gold(III) is selectively reduced into elemental gold (gold(0)) during the contact with CMA gel, the structure of which was transformed by the aid of boiling concentrated sulfuric acid so as to enhance the reduction reaction of gold(III). On this respect, we had reported the similar phenomena of the reductive adsorption of gold(III) by various biomass adsorbents such as orange juice residue, in which we reached the conclusion that the reduction of gold(III) is enhanced by the cross linked structure of polysaccharides such as cellulose formed by condensation reaction using boiling concentrated sulfuric acid and inferred the mechanism of the reductive adsorption of gold(III) as shown below [13][14][15][16]. The maximum adsorption capacities of gold (III) (q max ) were evaluated from the constant values at plateau region for each concentration of hydrochloric acid.…”
Section: Formation Of Elemental Gold On Cma Gelmentioning
confidence: 57%
“…Reference Cross-linked lignophenol prepared from sawdust of cedar 374 [3] Cross-linked lignocatechol prepared from sawdust of cedar 472 [3] Cross-linked lignopyrogallol prepared from sawdust of cedar 374 [3] Cross-linked lignophenol prepared from rice straw 552 [5] Cross-linked lignophenol prepared from wheat straw 217 [5] Cross-linked cellulose 1491 [25] Cross-linked dextran 1418 [25] Cross-linked alginic acid 1111 [25] Cross-linked pectic acid 946 [25] Cross-linked paper 1005 [10] Cross-linked cotton 1221 [11] Persimmon extract powder (PT powder, feed material of CPT)…”
Section: Adsorbent Maximum Adsorption Capacity (G/kg)mentioning
confidence: 99%
“…In our recent studies, we found that adsorption gels prepared from various kinds of biomass materials including various biomass wastes, i.e., bioadsorbents, exhibit high selectivity and high loading capacity for targeted metals such as hazardous heavy metals and valuable metals. These are prepared from waste wood [1][2][3][4] and straws of rice and wheat [5], spent papers [6][7][8][9][10], cotton [11], waste seaweeds [12,13], persimmon tannin [14][15][16] or wastes of persimmon [17,18] and grape [19,20] rich in tannin compounds, wastes of citrus such as orange [21] and lemon [22], and residue of microalgae after extracting biofuel [23,24].…”
Section: Introductionmentioning
confidence: 99%